2013
DOI: 10.1017/s0029665113003315
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of fruit and vegetable consumption in a cohort of Ghanaian women and evaluation of knowledge, attitudes and practice

Abstract: Non-communicable diseases (NCDs), previously confined to industrialised nations, are spreading through the developing world at unprecedented rates (1) . With communicable diseases still prevalent, this imposes a double-burden of disease in countries with limited resources and ill-equipped health systems (2) . An unhealthy diet, including insufficient consumption of fruit and vegetables is one of four main behavioural risk factors in the development of NCDs. However, consumption across the world, including Ghan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…In this study, we found the prevalence of fruits and vegetables consumption among the mothers to be relatively low. Studies conducted in Ghana have also reported similar findings [ 36 , 37 ]. Azupogo et al [ 36 ] reported that, vegetable intake among women in Northern Ghana was lower than WHO [ 38 ] recommended daily intake of at least 400 g per day.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In this study, we found the prevalence of fruits and vegetables consumption among the mothers to be relatively low. Studies conducted in Ghana have also reported similar findings [ 36 , 37 ]. Azupogo et al [ 36 ] reported that, vegetable intake among women in Northern Ghana was lower than WHO [ 38 ] recommended daily intake of at least 400 g per day.…”
Section: Discussionsupporting
confidence: 69%
“…Azupogo et al [ 36 ] reported that, vegetable intake among women in Northern Ghana was lower than WHO [ 38 ] recommended daily intake of at least 400 g per day. Similarly, a study conducted by Moss and Mushtaq [ 37 ] among 74 Ghanaian women reported 69% of the study participants to have low fruit and vegetable consumption patterns. In Ghana, low consumption of fruits and vegetables has been reported to be driven by a myriad of contextual and socioeconomic factors including age and household wealth [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 79%